A Linguistics Technique of Twentieth Century’s Spiritual Writers: Exploring the Language and Style of Twentieth Century's Spiritual Writers (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Since style is a concept that is likely familiar to the reader, a detailed explanation issuperfluous. Rather, it makes more sense to compare and contrast the two writers' and the spiritualwriting genre's diverse approaches to style, technique, and language. One of the primary focuses of thisthesis is an analysis of the spiritual writers' use of language and style, alongside an analysis of theirinspiring messages. The spiritual ties between the East and West were strengthened by their commonlanguage.